2013
DOI: 10.3389/fnhum.2013.00004
|View full text |Cite
|
Sign up to set email alerts
|

Postural correlates with painful situations

Abstract: Background: Emotional context may play a crucial role in movement production. According to simulation theories, emotional states affect motor systems. The aim of this study was to compare postural responses assessed by posturography and electromyography when subjects were instructed to imagine themselves in a painful or a non-painful situation.Methods: Twenty-nine subjects (22.3 ± 3.7 years) participated in this study. While standing quietly on a posturographic platform, they were instructed to imagine themsel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
36
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 48 publications
5
36
0
1
Order By: Relevance
“…Moreover, they concur with studies in humans reporting that the observer's body freezes during passive observation of aversive and arousing stimuli (Azevedo et al, 2005;Eerland, Guadalupe, Franken, & Zwaan, 2012;Facchinetti, Imbiriba, Azevedo, Vargas, & Volchan, 2006;Hillman, Rosengren, & Smith, 2004;Horslen & Carpenter, 2011;Lelard et al, 2013;Roelofs, Hagenaars, & Stins, 2010;Stins et al, 2011). Remarkably, our study significantly expands these observations by revealing a possible early cortical mechanism for implementing these motor reactions to emotional and, in particular, fear-related cues in humans.…”
Section: Icf Sicisupporting
confidence: 91%
“…Moreover, they concur with studies in humans reporting that the observer's body freezes during passive observation of aversive and arousing stimuli (Azevedo et al, 2005;Eerland, Guadalupe, Franken, & Zwaan, 2012;Facchinetti, Imbiriba, Azevedo, Vargas, & Volchan, 2006;Hillman, Rosengren, & Smith, 2004;Horslen & Carpenter, 2011;Lelard et al, 2013;Roelofs, Hagenaars, & Stins, 2010;Stins et al, 2011). Remarkably, our study significantly expands these observations by revealing a possible early cortical mechanism for implementing these motor reactions to emotional and, in particular, fear-related cues in humans.…”
Section: Icf Sicisupporting
confidence: 91%
“…O estudo evidenciou que ocorre diminuição na amplitude e frequência de deslocamento do CP no sentido AP na medida em que aumenta o nível de ameaça postural (plataforma elevada) [12]. Esta diminuição na oscilação postural provavelmente está relacionada com o fenômeno de congelamento postural [35,36], que é observado em participantes que visualizam imagens desagradáveis (pessoas multiladas ou com dor) [35,37,38]. Recentemente, foi eviden-ciado que estudantes submetidos a eventos ansiogênicos (como o período de provas) apresentaram mudanças no controle postural ortostático [39].…”
Section: Discussionunclassified
“…The ability to simulate another person's emotional response in a particular situation could be the basis for the development of empathic skills (Meltzoff & Decety 2003) and the instruction to adopt another person's perspective modulates pain rating according to the affective link between the observer and the individual experiencing the outcome (Singer et al 2006). In a first study (Lelard et al 2013), we used posturography to record differential postural responses when participants were instructed to imagine themselves in a painful or non-painful situation within the functional context of empathy for pain. This study demonstrated for the first time a stiffening response to pain visual stimulation, showing that postural responses were dependent of the perceived pain during the induced simulation process.…”
Section: Introductionmentioning
confidence: 99%